Jane Austen's geographies - Clark, Robert, 1948- (Andover : Routledge Ltd., 2018)
When Jane Austen represented the ideal subject for a novel as "three or four families in a country village", rather than encouraging a narrow range of reference she may have meant that a tight focus was the best way of understanding the wider world. The essays in this collection research the historical significance of her many geographical references and suggest how contemporaries may have read them, whether as indications of the rapid development of national travel, or of Britain s imperial status, or as signifiers of wealth and social class, or as symptomatic of political fears and aspirations. Specifically, the essays consider the representation of colonial mail-order wives and naval activities in the Mediterranean, the worrisome nomadism of contemporary capitalism, the complexity of her understanding of the actual places in which her fictions are set, her awareness of and eschewal of contemporary literary conventions, and the burden of the Austen family s Kentish origins, the political implications of addresses in London and Northamptonshire. Skilful, detailed, and historically informed, these essays open domains of meaning in Austen s texts that have often gone unseen by later readers but which were probably available to her coterie readers and clearly merit much closer critical attention.
List of illustrations Preface and Acknowledgements Standard References chapter 1 Introduction Robert Clark chapter 2 Conjugal Excursions, at Home and Abroad, in Jane Austen s Juvenilia and Sanditon (1817) John C. Leffel chapter 3 Emotional and Imperial Topographies Mapping Feeling in Catharine, or the Bower Ana-Karina Schneider chapter 4 Tales of Inheritance from West Kent 1 Mark Ballard chapter 5 Wessex Tales The West Country Background to Jane Austen Pat Rogers chapter 6 Traveling Shoe Roses The Geography of Things in Austen s Works Beth Kowaleski Wallace chapter 7 Slight and Fugitive Indications Some Locations in Sense and Sensibility and Pride and Prejudice Robert Clark chapter 8 r
Includes bibliographical references (pages ix-x) and index
Keywords: Austen, Jane, -- 1775-1817 -- Criticism and interpretation; Austen, Jane, -- 1775-1817 -- Knowledge -- Geography; Austen, Jane, -- 1775-1817 -- Settings; Women and literature -- England -- History -- 19th century; Setting (Literature); Geography and literature